PENGARUH GAYA KEPEMIMPINAN KEPALA DESA TERHADAP PELAKSANAAN PROGRAM PEMBANGUNAN DI DESA MALA TIMUR KECAMATAN MELONGUANE - MISAH, MEILANY; RARES, JOYCE JACINTA; DENGO, SALMIN (Sam Ratulangi University, 2019)
Leadership style is a pattern of behavior and strategies that are liked and often applied by leaders, by unitingorganizational goals with individual or employee goals, in order to achieve goals or objectives that havebecome joint commitments. The Village Head is a local government tool and village government tool tocarry out village governance, carry out village development, and foster village community development, andempower village communities. Village development as a process with the efforts of the village communityconcerned is integrated with the authority of the government to improve the economic, social and culturalconditions of the community and the possibility of them being given a full contribution to national progress.Based on this study, the village head's leadership style still had problems in realizing the implementation ofvillage development, among others the leadership of the village head was still less open, a vision that wasnot maximized for future orientation, lack of managerial abilities, leaders did not always evaluate the tasksgiven to subordinates. The research objective is to measure how much influence the village head'sleadership style has on the implementation of the development program in Mala Timur Village, MelonguaneDistrict. By using quantitative research methods. The sample of this study amounted to 44 people. Theinstruments used were the Likert scale and interview guidelines to get a score of the leadership style of thevillage head and the implementation of the development program. The test used in this study is the validityand reliability test and the techniques used are simple linear regression analysis and product momentcorrelation analysis techniques.Keywords: Leadership, Village Head, Development